Financial resources: how to manage them - Kraten, Michael (Henry Stewart Talks, 2011)
Assets, Liabilities, Net worth, Cash flows, Working capital, Fixed assets, Resource assessment, Cost of capital, Time value of money, Present value, NPV, Future value, Internal rate of return, IRR, Financial covenants, Debt covenants, Current ratio, Free cash flow, Personal guarantor, Revolving credit line, Unsecured loans, Secured loans, Convertible debt, Private equity, Venture capital, Going public, Asset liquidation, Sales and leasebacks, Joint ventures, Securitization, Collateral, Factoring receivables, Pricing strategy, Discounts, Contingent events, Environmental liability, Insurance, Risk Management, Cost / benefit analysis, Damage control strategy, Fund raising policy